Divine mania: alteration of consciousness in ancient Greece - Ustinova, Julija B. (Routledge, 2017)
chapter Introduction -- chapter 1 Prophetic mania -- chapter 2 Telestic mania and near-death experiences -- chapter 3 Bakcheia -- chapter 4 Mania on the battlefi eld and on the march -- chapter 5 Nympholepsy -- chapter 6 Poetic mania -- chapter 7 Erotic mania -- chapter 8 The philosopher’s mania and his path to truth.